(untitled) (Africa Development, 1983)
CONTENTS The Influences of Multinational Corporations on the Management of Public Enterprises in Nigeria H. A. ASOBIE .......................... 5 Τechnologie et Développement : Crise et Alternatives Azzam MAHJOUB ..................... 31 Organizational Form and Control of Parastatals in Tanzania R. S. MUKANDALA ..................... 58 State Policies in Production, Marketing and Pricing of Food Grains : The Case of Ethiopia Alemayehu LIRENSO ..................... 72 Quel Plan Marshall pour l'Afrique J. TEDAJO ........................ 85 DOCUMENT An Appeal from the Third World Forum to the Non Aligned Summit ................... 102 BOOK REVIEWS Economics of African Agriculture Toyin FALOLA .........................106 FOCUS ON RESEARCH AND TRAINING INSTITUTES The Association of Partially or Totally French-speaking Universities (AUPELF) ................. 109 BOOKS RECEIVED ................ 112